Follow-up and screening for type-2 diabetes mellitus in women with previous gestational diabetes in primary care - Amanda Björk Javanshiri; Susanna Calling; Sara Modig (Taylor & Francis Group, 2023)
AbstractObjective Gestational diabetes mellitus (GDM) is an established risk factor for developing type 2 diabetes mellitus (T2DM) that is possible to prevent by systematic follow-up and preventive measures. The aim of this study was to examine whether women with previous GDM were offered follow-up in primary care, according to Swedish national guidelines.Design Retrospective review of electronic medical records.Setting Primary care in southern Sweden, Skåne county.Subjects Women who received a GDM diagnosis in 2018 at the Endocrinology department, Skåne University Hospital in Lund. The study population consisted of a total number of 161 patients, whereof 83 patients were included.Main outcome measures Whether primary care offered follow-up for T2DM after GDM and if any communication took place between secondary and primary care. Furthermore, it was examined whether the quality of the follow-up was in accordance with the national guidelines.Results Of the study population, a total of 29% (n = 24) had been followed-up by primary care. In 55% (n = 46) of the cases, there was no communication between secondary and primary care. Plasma glucose was checked in all (n = 20) cases where follow-up could be evaluated. Conversations about lifestyle habits took place in 70% (n = 14) of the cases. Weight and risk factors for cardiovascular disease were controlled in less than half (n = 9) of the patients. Lifestyle advice was offered in two cases and in 24% (n = 20) of the cases an annual check-up was planned.Conclusions The follow-up of women with previous GDM in primary care in southern Sweden was lacking in seven out of 10 cases and showed great potential for improvement.Key PointsGestational diabetes is an established risk factor for developing type 2 diabetes.Earlier research has recognized that risk reduction is possible by systematic follow-up and preventive measures, but the extent of follow-up in primary care in southern Sweden remains unknown.This study demonstrates a lack of follow-up according to national guidelines for women with previous gestational diabetes in primary care in southern Sweden.There is great potential to improve the care of these patients with relatively simple means.